Maximum Biomass Co-Firing Percentage Mixture on 100 MW Pulverized Coal Boiler Using GateCycle Simulation Modelling - Febriant, FX Adeodatus Alfa; Firdaus, Reza; Khoir, Miftahul (Department of Mechanical and Industrial Engineering, 2025)
Abstract—For establishing Indonesia’s NZE target in 2060, biomass co-firing in existing Coal Fired Power Plant (CFPP) is one of the best and applicable method. This paper shows maximum biomass percentage on 100 MW scaled PC Boiler CFPP can handle by using GateCycle simulation. From the simulation, by increasing biomass mixture entering the furnace, it will increase total fuel flow in order to produce 100 MW. Biomass mixtures higher than 8% will tend to required total fuel flow exceeding maximum mill capacity which is 45,000 kg/hour, or reduced Generator Load while setting total fuel flow entering furnace same with maximum mill capacity. For every 1% increasing biomass mixture above 8%, it will reduced Gross Generator Load by 0.7505 MW. Increasing will also potentially increase slagging rate as the furnace temperature calculated from GateCycle simulation is 1,258.11 0C to 1,276.07 0C, while the ash fusion temperature of biomass is 1,185 0C. Also, increasing 1% of biomass mixture will increase the Specific Fuel Consumption by 0.0028 kg/kwh. From the simulation it is stated that maximum biomass percentage allowed for PC Boiler is 8%.